Eating habits, anthropometry, lifestyle, and hypertension of a group of non-village indigenous women in Amazon, Brazil - Rodrigues, Kleber Prado Liberal [UNESP]; Valadares, Ana; Pereira, Hilka Alves [UNESP]; Schiave, Quelly [UNESP]; Filho, Agnaldo Lopes Silva [UNESP] (FapUNIFESP (SciELO), 2023)
OBJECTIVE: The aim of this study was to describe the anthropometric characteristics, eating habits, and lifestyle of non-village indigenous women living in Manaus, AM, and their association with hypertension. METHODS: This cross-sectional (descriptive-Analytical) study was carried out from January 2020 to December 2021 using a questionnaire for clinical, sociodemographic, and behavioral data. Non-pregnant women who belonged to Parque das Tribos for more than a year, declared themselves indigenous, and were over 18 years of age were included in the study. RESULTS: In total, 21 ethnicities were identified, and 95 indigenous women were evaluated. The average age group was 36±12.1 years, the average height was 157 cm, and the body mass index was 28.8 kg/m2. The prevalence of systemic arterial hypertension was ±40%, and 68.5% had excess weight, with 29.1% having class I obesity. In all, 35.8% consumed a lot of salt, sugar, and industrialized foods, and 88.4% were sedentary. CONCLUSION: Much of the sample presented excess weight, and almost all were sedentary. More than one-Third had unappropriated eating habits. Hypertension was present in more than one-Third of these indigenous women. There was an association between higher body mass index and hypertension. Knowing the characteristics of this group of non-village indigenous women may help determine the best health approach. The data demonstrate the necessity of preventive measures.
Keywords: Anthropometry; Comorbidity; Indigenous peoples.; Obesity